Effect of glycerol as plasticizing agent on the mechanical properties of Polyvinly alcohol/banana peel powder blend film - Tan, Yee Ling (2022)

(untitled)
Nowadays, plastic pollution become more serious because the plastic bag that appear at the market is made from petroleum-based plastic which is difficult to degrade. Hence, biodegradable plastic is introduced to solve this serious problem. Polyvinyl alcohol (PVA) can blend with banana peel powder (BPP) to form a biodegradable film which can be degrade easily. Different composition of glycerol was added into the blend film to investigate the mechanical properties of the PVA/BPP blend film. PVA/BPP blend films were prepared by using solution casting method. The BPP and PVA/BPP blend film were analyse by using Attenuated Total Reflectance Spectroscopy (ATR), Thermogravimetric Analysis (TGA) and biodegradability test. Besides, the mechanical properties of PVA/BPP blend films were analyse by using tensile test which is to determine its tensile strength, elongation at break and Young’s modulus. When increase the composition of glycerol, the tensile strength and Young’s modulus of the blended film will decrease respectively. However, the elongation at break will increase as the composition of glycerol increase. The tensile strength and Young’s modulus of PVA/BPP blend films that without glycerol (6.65MPa, 81.9MPa) will higher than the PVA/BPP blend film in the presence of glycerol (4.318MPa to 3.616MPa, 49.99MPa to 30.14MPa). Moreover, the elongation at break of the PVA/BPP blend film which contain glycerol (34.27% to 48.31%) is higher than PVA/BPP blend film that without glycerol (32.72%). After 2 weeks of biodegradability test, PVA/BPP blend films which contain 2ml of glycerol has the highest biodegradability rate (11.55%) among other PVA/BPP blend films.